2019
DOI: 10.1111/are.14080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous magnetic field exposure on water properties and subsequent effects on the growth performance, plasma biochemistry, nutritive value and liver histopathology of Jade PerchScortum barcooin a recirculating system

Abstract: A 150-days study was conducted on the continuous exposure of magnetized water at 0.00, 0.10, 0.15 and 0.20 Tesla (T) on quadruplicate treatments of Jade Perch Scortum barcoo juveniles in a recirculating system. Each replicate consisted of 18 fish with an average weight of 7.52 g over all treatments. The feeding efficiencies, growth, whole-body proximate plasma parameters, survival were measured and liver histopathology was observed. Our results show no significant improvement in water quality parameters, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
3
13
2
Order By: Relevance
“…Water temperature in the fish tanks was around the average of 24°C, which is within the optimum temperature of common carp foraging and growth (24 and 28 °C) reported byOyugi, et al (2012).The overall means of NH 4 -N, NO₂-N and NO 3 -N concentrations in fish tanks did not differ significantly (P>0.05) between the electromagnetic field system and the control system (Table2). The results of the present study are comparable with the findings of various authors(Krzemieniewski et al, 2004;Hassan et al, 2018a;Hassan et al, 2019) who found no changes in ammonium concentrations between the magnetic field system and the control system. However, the results of this study were in contrast with the findings obtained byRahman (2016), andHassan et al (2018b) who found a reduction in the ammonium concentrations of the magnetic treatments.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Water temperature in the fish tanks was around the average of 24°C, which is within the optimum temperature of common carp foraging and growth (24 and 28 °C) reported byOyugi, et al (2012).The overall means of NH 4 -N, NO₂-N and NO 3 -N concentrations in fish tanks did not differ significantly (P>0.05) between the electromagnetic field system and the control system (Table2). The results of the present study are comparable with the findings of various authors(Krzemieniewski et al, 2004;Hassan et al, 2018a;Hassan et al, 2019) who found no changes in ammonium concentrations between the magnetic field system and the control system. However, the results of this study were in contrast with the findings obtained byRahman (2016), andHassan et al (2018b) who found a reduction in the ammonium concentrations of the magnetic treatments.…”
supporting
confidence: 92%
“…Moreover, the stocking density of fish was probably below the carrying capacity of these systems and did not reach the threshold at which survival rates would be affected. The survival rates of fish in the present study (100%) were higher than the 80.9% survival rate reported by Krzemieniewski et al (2004) Hassan et al (2019) for Jade Perch Scortum barcoo juveniles reared in a RAS under the exposure of different magnetic field intensities. The higher survival rate was achieved in the present study might be related to the duration of exposure, the field intensity and the variation in the sensitivity of different species.…”
Section: Growth and Survival Rates Of Fishcontrasting
confidence: 79%
See 2 more Smart Citations
“…However, the application of the magnetic treatment in aquaculture sector is still a new approach of several studies have been conducted to test the effect of magnetic field on aquaculture as Jamabo et al (2016); ) & Hassan et al (2019. Therefore, the purpose of this study was to evaluate the influence of using magnetic treated water and stocking density on water quality, growth performance, feed utilization, body composition and blood parameters of Nile Tilapia (Oreochromis nilolicus).…”
Section: Intoductionmentioning
confidence: 99%